The effect of mindfulness-based stress reduction program applied to postmenopausal women on insomnia and quality of life - Cetin, Nurdilan Sener; Nacar, Gulcin; Tashan, Sermin Timur (Routledge Journals, Taylor & Francis Ltd, 2024)
This study aimed to determine the effect of the mindfulness-based stress reduction program applied to postmenopausal women on insomnia and quality of life. A quasi-experimental pretest-posttest control group design was used. The sample of the study consisted of a total of 151 postmenopausal women, including 73 in the experimental group and 78 in the control group. In the study, the mindfulness-based stress reduction program (MBSR) was applied to the women in the experimental group for eight weeks, and then the women repeated the program individually for another eight weeks. The second measurement data were collected eight weeks after the collection of the first measurement data, and the third measurement data were collected 16 weeks later. The mean score obtained from the second measurement application of the Women's Health Initiative Insomnia Rating Scale (WHIIRS) was lower in the experimental group than in the control group (p < .05). In addition, the mean scores from the second and third measurement applications of the Menopause-Specific Quality of Life Questionnaire (MENQOL) were lower in the experimental group than in the control group (p < .05). The MBSR program reduced postmenopausal women's insomnia and improved their quality of life. This program can be used safely to treat insomnia and improve the quality of life of postmenopausal women.
Keywords: Insomnia; mindfulness; mindfulness-based stress reduction program; postmenopausal women; quality of life